Amiodarone-induced vasculitis and polyserositis. Issue 713 (March 1985) - Stäubli, M.; Zimmermann, A.; Bircher, J.
Abstract : A dose-dependent cutaneous leukocytoclastic vasculitis developed in a 34 year old man who was given amiodarone for supraventricular tachycardias resistant to other drugs. This adverse reaction disappeared within 2 weeks after discontinuation of amiodarone despite its very long half-life of 52 days in this patient. During previous treatment periods with amiodarone, the patient had experienced photosensitivity and dose-dependent polyserositis. Since high doses of amiodarone have been recently proposed for the treatment of resistant cardiac arrhythmias, dose-dependent adverse effects as described here may be encountered with increasing frequency.